IMITASI BAHASA SELEBGRAM DAN DAMPAKNYA TERHADAP PRAKTIK BERBAHASA REMAJA DI KOTA MATARAM: KAJIAN PRAGMATIK SIBER - Wika Wahyuni; I Nyoman Sudika; Januari Rizki Pratama; Ahmad Rifai; YY Wima Riyayanatasya; Citra Aulia Putri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to examine the forms of imitation of Instagram celebrity language and its impact on the language practices of adolescents in Mataram City from a cyber pragmatics perspective. The scope of the study includes identifying the Instagram celebrity language styles imitated by adolescents and their implications for language use in digital communication and everyday life. This study used qualitative methods with data collection techniques in the form of observations, interviews, and questionnaires with adolescents who are active Instagram users. Data were analyzed using content analysis techniques with reference to cyber pragmatics theory and social imitation theory. The results show that adolescents tend to imitate the use of Instagram celebrity language (such as kocak, anjay, yapping, for real, gacor, etc.) in their communication with an average percentage of 72.55%. This imitation occurs not only in digital spaces, but also in offline interactions. The impact is seen in the shift in language styles to more informal and the emergence of a tendency to use language that pays less attention to communication ethics. These findings indicate that Instagram celebrities play a role as linguistic models that influence adolescents' language practices in the digital era.